Tan ( a + b ) = [ tan a + tan b ] / [ 1 - (tan a)*(tan b) ];
let be a = 2x and b = x;
=> tan 3x = [ tan 2x + tan x ] / [ 1 - (tan 2x)*(tan x) ] => (tan 3x)*[ 1 - (tan 2x)*(tan x) ] =
tan 2x + tan x => tan3x - tan 3xtan 2xtanx = tan 2x + tan x => <span> tan 3x−tan 2x−tanx = tan 3xtan 2xtanx.</span><span />
Here are some very good video that explain how. very short and easy too. http://virtualnerd.com/pre-algebra/linear-functions-graphing/rate-of-change-slope/finding-slope/slop... math antics on youtube is great for help too
(12½) ÷ (⅙) = (25/2) ÷ (⅙) = (25/2) × (6/1) =75